Application of Servqual for evaluation of quality of care in a Pharmacy situated in the city of Pau dos Ferros-RN (Research, Society and Development, 2019)
The quality of the services rendered is an influential and determining factor for the conquest of new clients, as well as for the loyalty of the existing clients. And for the quality of services to be measured in quantifiable values there are several analysis tools, among them is the Servqual tool, used in this article, which is based on the comparison of the client's expectations regarding a qualified service and the perception of clients with relation to the service purchased. In this context, the present study aims to evaluate the level of quality in the care of a pharmacy in the city of Pau dos Ferros – RN. The research presents a case study. As a collection method, a questionnaire with two dimensions, based on the Servqual model, was distributed in five dimensions of quality: Tangibility, Reliability, Responsiveness, Security and Empathy, using the seven-point Likert scale. The analysis of the data was made based on the comparison of the two questionnaires of the respondents. The results reveal the degree of customer satisfaction, with emphasis on the dimensions of Tangibility, Security and Responsiveness. While the Reliability and Empathy dimensions presented critical factors regarding the satisfaction of their clients. From these results suggestions for improvement are presented, with the purpose of improving the quality grade in the dimensions that presented values below expectations.